The Prognostic Impact of Tumor Architecture for Upper Urinary Tract Urothelial Carcinoma: A Propensity Score-Weighted Analysis - Liu, Hui-Ying; Chen, Yen Ta; Huang, Shun-Chen; Wang, Hung-Jen; Cheng, Yuan-Tso; Kang, Chih Hsiung; Lee, Wei Ching; Su, Yu-Li; Huang, Chun-Chieh; Chang, Yin-Lun; Chuang, Yao-Chi; Luo, Hao Lun; et al. (Frontiers in Oncology, 2021)
Purpose To assess the association of tumor architecture with cancer recurrence, metastasis, and cancer-specific survival (CSS) in patients treated with radical nephroureterectomy (RNU) for upper urinary tract urothelial carcinoma (UTUC) in Taiwan. Materials and Methods Data were collected from 857 patients treated with RNU between January 2005 and August 2016 in our hospital. Pathologic slides were reviewed by genitourinary pathologists. Propensity score weighting was performed for data analysis. Results Sessile growth pattern was observed in 212 patients (24.7%). Tumor architecture exhibited a significant association with bladder cancer history, chronic kidney disease (CKD), tumor stage, lymph node status, histological grade, lymphovascular invasion, concomitant carcinoma in situ, and the variant type [standardized mean difference (SMD) > 0.1 for all variables before weighting]. In the propensity score analysis, 424 papillary and sessile tumor architecture were analyzed to balance the baseline characteristics between the groups. Tumor architecture was an independent predictor of metastatic disease and CSS (p = 0.033 and p = 0.002, respectively). However, the associations of tumor architecture with bladder and contralateral recurrence were nonsignificant (p = 0.956 and p = 0.844, respectively). Conclusions Tumor architecture of UTUC after RNU is associated with established features of aggressive disease and predictors of metastasis and CSS. Assessment of tumor architecture may help identify patients who could benefit from close follow-up or early administration of systemic therapy after RNU. Tumor architecture should be included in UTUC staging after further confirmation.